China’s Relationships with Sub-Saharan Africa: Despite Convergence with Industrialised Countries, Drivers of Structural Transformation? - (:unkn) unknown (My University, 2014)
China has become a major partner of Sub-Saharan African economies since the early-2000s. It is argued that China’s trade and investment patterns converge with those of developed countries, but also that they may foster structural transformation. Sub-Saharan African growth rates since the early-2000s are driven by China’s demand for goods produced in Sub-Saharan Africa and its contribution to high commodity prices. Yet these growth rates stem from distorted export structures, and may strengthen commodity-dependence. Against these views, the paper argues that Sub-Saharan Africa’s growth rates and commodity prices may stay high, as China’s growth is expected to remain sustained, and a long period of high growth rates and fiscal room for manoeuvre may foster structural transformation. Also, China is not exposed to the negative effects of conditional aid, and it invests in Sub-Saharan African infrastructure and industrial sectors, both being key determinants of structural transformation.
Keywords: African Research